Disponibilidade de biomassa e caracterização da caatinga sob manejo agroecológico - Silva, Beatriz Kelly Guedes da (2016)
The Caatinga occupies about 11% of the national territory, covering the states of Bahia, Sergipe, Alagoas, Pernambuco, Paraiba, Rio Grande do Norte, Ceará, Piauí and Minas Gerais. Native pastures have great importance for the world's livestock, particularly for the production of small ruminants in the Northeast. This work aimed to characterize the vegetation of Caatinga under agroecologica management, the same being discussed in theoretical and scientific paper for publication. The theoretical framework is reported descriptions of the Brazilian semiarid region in which highlights the vegetation characteristics of the Caatinga with forage potential and discusses its use in periods of drought and rain over the years. Also reports agroecologica features that help comes a better handling of the animals that feed on forage species in the Caatinga, addressing floristic structuring and phytosociological characterization for sustainable management, even in periods of drought. The paper depicts the study of the availability of dry matter, floristic composition and frequency, and the similarity of species of plant areas of Caatinga under agroecologica management. In this study, it raised the availability of dry matter, which showed variations in the periods influenced by the function of vegetation resilience of rain the previous cycle, with maximum peaks of dry matter, 1.005 kg DM / 0,25m² and 1.042 kg MS / 0,25m² respectively in October and April. In that experiment it was observed that the most frequent species were Euphorbiaceae, Fabaceae, Rubiaceae and Poaceae. To evaluate the similarity of species with the highest similarity were suaveolens Mesosphaeru (lavender), Tribulus terrestris L. (bull's head), Borreria verticillata (old head), Mimosa hostilis Benth (Jurema), Sida sp (mauve) and Aristida adscensionis L. (cocksfoot grass)